Analisis Strategi Bersaing Usaha Mikro Kecil dan Menengah (UMKM) di Masa Pandemi Covid-19 Dalam Perspektif Etika Bisnis Islam (Studi Pada Pelaku UMKM Keripik Pisang di Jl. ZA. Pagar Alam) - Siska Yuli Anita (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to find out how the competitive strategy that can be carried out by banana chip UMKM is and to find out how to compete with banana chips UMKM based on the perspective of Islamic business ethics. This type of research is field research, using data collection methods in the form of observation, documentation and literature study. The number of samples is 32 respondents. Using SWOT analysis (Strength, Weaknes, Opportunity, Threat) as an analysis tool. The results of the research on banana chips UMKM at the UMKM Center Jl Z.A Pagar Alam Bandar Lampung City have the potential to continue to grow. With the results from the SWOT diagram which is in quadrant I, namely an aggressive strategy so that it can be carried out by UMKM chips in the midst of the covid-19 pandemic, namely with internal strengths that take advantage of existing opportunities. Strengths that can be utilized during the current pandemic are the products offered by UMKM actors who are already well-known in the community. In addition, the chips UMKM business owners also have strategies that are in accordance with Islamic business ethics, namely amanah, fatonah, tabligh and shiddiq.